Investigation of the pressure coefficient impact on the air infiltration in buildings with respect to microclimate. (September 2017) - Charisi, Stergiani; Waszczuk, Milosz; Thiis, Thomas K.
Abstract: Wind pressure coefficients (Cp ) are important for calculating the air infiltration rate of a building. Cp depend on a wide range of parameters, such as wind direction and speed, position on the building surface and façade exposure. Most Building Energy Simulation (BES) programs generally calculate air infiltration using simplified pressure coefficients. The Norwegian technical software (SIMIEN) do not consider them. The effect of the pressure coefficients on the air infiltration of the building, taking into consideration the microclimate of the building area, is studied. The wind pressure coefficients are defined through computational fluid dynamics (CFD) simulations. The air infiltration in the building is determined based on the calculated pressure coefficients. Tracer gas measurements were used for validation of the results. Two cases of fully exposed and partially sheltered building were examined. The results indicate that wind pressure coefficients derived from CFD simulations calculate more realistic values for the air infiltration of the building.